2018
DOI: 10.18404/ijemst.440335
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Case Analysis of Engineering Education Experiences in Inclusive STEM-Focused High Schools in the United States

Abstract: Article HistoryIn an attempt to broaden participation in STEM, a new type of high school is emerging, high schools which include a focus on engineering, have few or no academic admission criteria, and actively involve students of all levels of ability, known as Inclusive STEM High Schools (ISHSs). One aspect of successful ISHSs includes the intentional and explicit integration of engineering learning opportunities into coursework. The purpose of this paper is to report results of a systematic cross-case analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Interviewed teachers provided more nuanced perspectives, reporting increased confidence in teaching through questions and addressing student responses, using models during investigations, and emphasizing optimization and the iterative nature of engineering. These pedagogical skills allow teachers to foster students' ability to plan and carry out investigations (Duschl and Bybee 2014;Peters-Burton and Johnson 2018). It also became apparent that while teachers showed growth in their perceived ability to develop NGSS-aligned engineering lessons, more attention should be paid to open-ended design and cost effectiveness in future workshop sessions, which is consistent with prior research (Haag and Megowan-Romanowicz 2015;Shernoff et al 2017).…”
Section: Affective Impacts On Pedagogical Growthsupporting
confidence: 63%
“…Interviewed teachers provided more nuanced perspectives, reporting increased confidence in teaching through questions and addressing student responses, using models during investigations, and emphasizing optimization and the iterative nature of engineering. These pedagogical skills allow teachers to foster students' ability to plan and carry out investigations (Duschl and Bybee 2014;Peters-Burton and Johnson 2018). It also became apparent that while teachers showed growth in their perceived ability to develop NGSS-aligned engineering lessons, more attention should be paid to open-ended design and cost effectiveness in future workshop sessions, which is consistent with prior research (Haag and Megowan-Romanowicz 2015;Shernoff et al 2017).…”
Section: Affective Impacts On Pedagogical Growthsupporting
confidence: 63%
“…Our analysis of NSTA's articles also showed that engineering practices with heavier data components, such as OPT and EAN, were underutilized. According to Peters-Burton and Johnson (2018), modeling and analysis were also among the least prominent topics covered in the STEM-focused high schools they examined. Increased attention to these two inquiries of engineering (OPT and EAN) could help address the difficulties of integrating mathematics with science and engineering, especially at the high school level (Becker & Park, 2011;English, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This reform effort, with its ambitious framing, also necessitated an urgent need for improving curriculum, assessment, and teacher education in alignment with the new vision. To address this need, many researchers have focused on increasing teachers' familiarity with engineering and developing integrated curricula expanding across elementary (Capobianco & Rupp, 2014;Moore, Tank, Gajdzik, et al, 2015;Museum of Science, 2019;Wendell & Rogers, 2013) and secondary education (Cantrell, Pekcan, Itani, & Velasquez-Bryant, 2006;Apedoe, Reynolds, Ellefson, & Schunn, 2008;Daugherty & Custer, 2012;Silk, Schunn, & Cary, 2009;Peters-Burton & Johnson, 2018). In this position paper, we draw attention to the differences in arguments that shape integration practices and elucidate related confusions.…”
Section: Introductionmentioning
confidence: 96%